Toxic inhalational injury. Issue 3 (10th March 2020) - Davies, Victoria; Turner, Jake; Greenway, Michael
Abstract : A middle-aged patient presented with toxic inhalational injury, and was resuscitated prehospitally and treated in the emergency department for smoke inhalation, carbon monoxide (CO) exposure and cyanide poisoning with the use of antidotes. Due to the CO effects on spectrophotometry, an anaemia initially identified on blood gas analysis was thought to be artefactual, but was later confirmed by laboratory testing to be accurate. In addition, cyanide can confound haemoglobin testing due to its use in the analytical process and non-cyanide analysis is required when there is suspected exposure. Although no consensus exists on a first-line cyanide antidote choice, hydroxocobalamin is the only antidote without a serious side effect profile and/or deleterious cardiovascular effects. We propose prehospital enhanced care teams consider carrying hydroxocobalamin for early administration in toxic inhalational injury.